TINGKAT KEPATUHAN PENGGUNAAN OBAT ANTIDIABETES ORAL PADA PASIEN RAWAT JALAN DI UPTD PUSKESMAS TOMUAN KOTA PEMATANGSIANTAR TAHUN 2024 - Emi Sugesti; Meyana Marbun, Octavian Ashindo Nababan, Afriyanti Sihombing (CV. Adiba Aisha Amira, 2025)
The purpose of this study was to find out the description the level of adherence oral antidiabetic drug use in patiens outpatient treatment in UPTD Health center Tomuan City Pematangsiantar. The type of research used is an observational study using descriptive method.A total sampling technique is used with an amount 80 patients. The primary data collection instumen using Morisky Medication Adherence Scale 8 items (MMAS-8) questionnaire to see compliance rate of diabetes mellitus patient. The result of the study found that the level of adherence in using oral antidiabetic drugs in patients with in UPTD Tomuan health center Tomuan City Pematangsiantar said to be Low Compliance 47.5%, which was said to be Medium Compliance 27.5% Medium Compliance, which was said to be High Compliance 25%. Because many patients forgot to take their medicine yesterday and when the patient left the house the patient also forgot to take the medicine. Thus, it can be said that more patients with a level of compliance with the use of oral antidiabetic drugs are categorized as